Social Engagement among Migrant Youth: Attitudes and Meanings - Kirpitchenko, Liudmila (2014)
This article explores migrant young people’s engagement, participation and involvement in socially meaningful activities, events and experiences. This type of social participation is approached in the social inclusion literature using the notions of social capital and active citizenship (Bourdieu, 1986; Coleman, 1988; Putnam, 1993; Putnam, 2000). A key objective, therefore, is to explore the attitudes, values and perceptions associated with social participation for young people. They include the meanings that social engagement has for migrant young people, along with drivers and inhibitions to active participation. The article focuses on both the motives for being actively engaged as well as perceived barriers to social engagement. It is based on a large study conducted among migrant young people of African, Arabic-speaking and Pacific Islander backgrounds in Melbourne and Brisbane, and presents both quantitative and qualitative (discursive) snapshots from the overall findings, based on interviews and focus groups. While many studies have centred on the management of migration and migrants, this article draws attention to the individuals’ active position in negotiating, interpreting and appropriating the conditions of social inclusion. Accounting for the multidimensional and multilayered nature of social inclusion, the paper highlights the heuristic role of social engagement in fostering the feelings of belonging and personal growth for migrant youth.